PERANCANGAN IDENTITAS VISUAL PADA EVENT KEEP ON STAGE DI PREGINA SHOWBIZ BALI - Pranawa, I.G.A.Ngurah Bagus Rama; Nuriarta, I Wayan; Swandi, I Wayan (Program Studi Desain Komunikasi Visual, 2024)
Keep on Stage is a concept for a music performance event that is designed by Pregina Showbiz Bali with the intent to conserve the spirit to keep doing live performances on a stage. But, the Keep on Stage event does not yet have any visual identity to present itself to the public. Therefore, Keep on Stage needs a visual identity design that is strong so It can be recognized and remembered. This design uses the creation method developed by Hawkins on the book “Creating Through Dance” that is Exploration, Improvisation, and Formation. This design also uses method of collecting data like interview, observation, literature study, and documentation. This design creates brand visual identity like logo and illustration assets that is apllicated on promotion media like Instagram post, Billboard, T-Banner, T- Shirt, and Nametag. The idea of conserving the spirit of music performance that Pregina Showbiz Bali wants to show through Keep on Stage event are presented on the visual identity that have been designed.